Northern South China Sea Surface Circulation and its Variability Derived by Combining Satellite Altimetry and Surface Drifter Data - Benny, N. Peter (Chinese Geoscience Union, 2015)
The present study analyses the mean and seasonal mesoscale surface circulation of the Northern South China Sea (NSCS) and determines the influence of El Niño/Southern Oscillation (ENSO). High resolution Eulerian velocity field is derived by combining the available satellite tracked surface drifter data with satellite altimetry during 1993 - 2012. The wind driven current is computed employing the weekly ocean surface mean wind fields derived from the scatterometers on board ERS 1/2, QuikSCAT and ASCAT. The derived mean velocity field exhibits strong boundary currents and broad zonal flow across NSCS. The anomalous field is quite strong in the southern part and the Seasonal circulation clearly depicts the monsoonal forcing. Eddy Kinetic Energy (EKE) distribution and its spatial and temporal structures are determined employing Empirical Orthogonal Function (EOF) analysis. The ENSO influence on NSCS surface circulation has been analyzed using monthly absolute geostrophic velocity fields during 1996 - 1999.